Synergistic effects of carbon nanotubes and carbon fibers on heat generation and electrical characteristics of cementitious composites - Kim, G. M.; Yang, B. J.; Yoon, H. N.; Lee, H. K. (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
The heat generation and electrical characteristics of cementitious composites incorporating carbon nanotube (CNT) and carbon fiber under various heating conditions were investigated in this study. Specifically, the synergistic effects of carbon nanotube and carbon fiber on the heat generation and electrical characteristics of cementitious composites were experimentally investigated. The test results show that the addition of carbon fiber improved the heat generation capability and the electrical stability of the cementitious composites incorporating CNT during heating. The long-term durability of construction materials is an important issue, however, there is a practical limit to measuring a property of specimen for a very long time in a laboratory level experiment. In addition, a modified micromechanical model was proposed here to estimate the long-term effect of heating on the electrical characteristics of cementitious composites. The model parameters were derived from the experimental results, and a series of numerical simulations was conducted to explore the influence of model parameters on the resistance of the composites. Comparisons between experimental data and the present predictions were made to assess the potential of the proposed model. (c) 2018 Elsevier Ltd. All rights reserved.
Keywords: TEMPERATURE-COEFFICIENT; CONDUCTIVE CONCRETE; NANOCOMPOSITES; CNT; BEHAVIOR